Promosi Thibbun Nabawi melalui Word of Mouth dan Media Sosial: Perspektif Komunikasi Islam - Tika, Rostika Yuliani; Mutia, Lu’lu (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2025)
The growing interest of Muslim communities in alternative medicine, particularly thibbun nabawi, is closely related to the communication strategies used to promote it. This study aims to analyze the promotion of thibbun nabawi through word of mouth (WOM) and social media from the perspective of Islamic communication. A qualitative approach with a constructivist paradigm and case study method was employed at the Thibbun Nabawi Center, Babussalam Islamic Boarding School, Bandung. Data were collected through in-depth interviews, participatory observation, and documentation over the course of one month. The findings indicate that WOM serves as the primary promotional channel, as it is based on patients’ real experiences and reinforced by recommendations from primary groups such as family and friends. Social media acts as a supporting channel that expands the reach of information and strengthens the Islamic image through digital da’wah content. The integration of WOM, social media, and Islamic values contributes to building a positive image of thibbun nabawi as an alternative health service aligned with Islamic teachings, thereby increasing public acceptance. This study contributes to the development of Islamic communication literature, particularly in the field of health promotion based on religious values, while also offering practical implications for Islamic health service providers to optimize the combination of personal and digital promotion strategies.